Utilization of Swamp Forages from South Kalimantan on Local Goat Performances - T Rostini; L Abdullah; K G Wiryawan; P D.M.H Karti (Media Peternakan, 2014)
Forages in swamp area consist of grass and legumes that have good productivity and nutrient quality. This research was aimed to evaluate the potency of swamp forage on digestibility and performance of goats. There were 24 local male goats aged 10-12 months with initial body weight of 13.10±1.55 kg, allocated into 6 treatments. Those were control (R0): 60% grass and 40% legumes; (R1): 60% swamp forages and 40% concentrate; (R2): 100% swamp forages; (R3): 100% swamp forage hay; (R4): 100% swamp forage silage; (R5): 100% haylage swamp forages. Results showed that silage treatment significantly increased (P<0.05) consumption and digestibility. Swamp forages could be utilized well by preservation (silage, hay, and haylage). Ensilage of swamp forages increased protein content  from 13.72% to 14.02%, protein intake (74.62 g/d), dry matter intake (532.11 g/d), nitrogen free extract intake (257.39 g/d), with total body weight gain (3.5 kg) in eight weeks and average daily gain (62.60 g/d). It is concluded that ensilage of swamp forages (R4) is very potential to be utilized as forage source for ruminants such as goats. Key words: body weight, goat, haylage, silage, swamp forage